Queering Anti-Zionism: Academic Freedom, LGBTQ Intellectuals, and Israel/Palestine Campus Activism - Blackmer, Corinne E. (Wayne State University Press, 2022)
"This book explores the work of five influential pro-BDS (Boycott, Divestment, and Sanctions) queer academic activists-Sarah Schulman, Jasbir Puar, Angela Davis, Dean Spade, and Judith Butler-each of whom exemplify different ideological and critical practices around anti-Zionism"–
Keywords: Boycotts; Foreign public opinion; Israel; Boycott; divestment; and sanctions movement; Zionism; Gay rights; Israel; Israel; Disinvestment; Politics and government; dept.eng; faculty_collection